Influence of the cable´s layout on the shearing resistance of prestressed concrete beams - SOUZA JUNIOR,O. A. (2016)
Abstract Little information on experimental investigations regarding the influence of the prestressing forces in the shear resistance of prestressed beams is found in the technical literature. Thus, it was experimentally evaluated the shear resistance of six post-tensioned prestressed concrete beams with cross section of (150 x 450) mm2, total length of 2400 mm and concrete's compressive resistance of 30 MPa, with the variables of this work being the layout of the prestressing cable, straight or parabolic, and the stirrups geometric rate. Verticals displacement, steel and concrete's strains and a comparison of the experimental loads with the estimates of ACI 318, EUROCODE 2 and NBR 6118: 2014 codes are presented and discussed. The results showed that the cable's parabolic layout increased the beams' shear resistance in up to 16% when compared to beams with straight cables.